Scanning probe microscopy for industrial applications : nanomechanical characterization - Yablon, Dalia G., 1975- (Hoboken, New Jersey : John Wiley & Sons, 2013)
'Covering a diverse range of practical applications and real-world examples, Scanning Probe Microscopy for Industrial Applications examines important and successful applications of SPM in various industries, including food science, personal care industry, and forestry applications. Author D. G. Yablon details how SPM has impacted the industrial sector leading to improved product formulation, new understanding of processes, and improvements in manufacturing. The book provides chemists, materials scientists, physicists, polymer scientists, and biophysicists with the most important and successful applications of SPM'--
'This book broadly addresses the use of Scanning Probe Microscopy (SPM) for industrial applications and provides a resource that focuses on the use of SPM for real world applications'--
Machine generated contents note: Preface and Acknowledgements Chapter 1 Overview of Atomic Force Microscopy Chapter 2 Understanding the tip-sample contact: an overview of contact mechanics from the macro to the nanoscale Chapter 3: understanding surface forces using static and dynamic approach/retraction curves Chapter 4: Phase Imaging Chapter 5: Dynamic contact AFM methods for nanomechanical properties Chapter 6: Best Practices in AFM Imaging Chapter 7: Nanoindentation measurements of Mechanical properties of very thin films and nanostructured materials at high spatial resolution Chapter 8: SPM for Critical Measurements in the Semiconductor Industry Chapter 9: SPM for Polymer Applications in the Chemicals Industry Chapter 10: Unravelling links between food structure and function with probe microscopy Chapter 11: Microcantilever Sensors For Petrochemical Applications Chapter 12: Applications of SPM in cosmetic Science Chapter 13: Applications of Scanning Probe Microscopy and Nanomechanical Analysis in Pharmaceutical Development Chapter 14: A comparative nanomechanical study of multiharmonic force microscopy and nanoindentation on low dielectric constant materials Chapter 15: Nanomechanical Characterization of Biomaterial Surfaces: polymer coatings that elute drugs .
Includes bibliographical references and index.
Keywords: Materials -- Microscopy; Scanning probe microscopy -- Industrial applications